Contractual Obligations of Transnational Corporations under Human Rights Law: A Critical Analysis - Saeeda Mirbaz*; Dr. Faiz Bakhsh (Dialogue Social Science Review (DSSR), 2025)
Transnational Corporations (TNCs) play a dominant role in global commerce, often engaging in complex contractual relationships across multiple jurisdictions. As their influence grows, so too does the scrutiny of their impact on human rights. This research article critically examines the contractual obligations of TNCs under international human rights law, exploring how contractual mechanisms can both advance and undermine human rights protections. Traditionally, international human rights law imposes obligations primarily on states; however, evolving legal norms and practices are increasingly recognizing the role of private actors, particularly TNCs, in respecting human rights standards through their contractual arrangements. The paper analyzes key instruments such as the UN Guiding Principles on Business and Human Rights and explores how contractual clauses such as human rights due diligence, supplier codes of conduct, and third-party beneficiary rights are being used to embed human rights obligations into business operations. It also identifies limitations in enforcement, the imbalance of bargaining power, and the voluntary nature of many such clauses. The article concludes by proposing legal and policy reforms to strengthen the accountability of TNCs through binding contractual frameworks aligned with international human rights norms. Keywords: Transnational Corporations (TNCs), Human Rights Law, Contractual Obligations, Corporate Accountability, Due Diligence.